Propuesta para la enseñanza de internet de las cosas bajo el enfoque del diseño universal para el aprendizaje - Andrade Coronado, Anderson Gustavo (2024)
The research conducted at the Quevedo State Technical University, under the direction of Anderson Gustavo Andrade Coronado, presents an innovative methodological proposal for teaching the Internet of Things (IoT) by applying the principles of Universal Design for Learning (UDL). This proposal seeks to overcome traditional educational barriers by integrating adaptive technologies and inclusive pedagogical strategies, in order to provide an accessible learning experience for all students. Through the use of multiple means of representation, expression and engagement, it seeks to foster an educational environment that caters to the diversity of learning needs and preferences. The methodology adopted is qualitative, with an applied design, focused on the integration and evaluation of an educational system that promotes inclusion and equity in the IoT field. It focuses on identifying technological tools and resources that enrich the teaching-learning process, allowing students to explore and express their knowledge effectively. Active collaboration between teachers and students is fundamental in the analysis and evaluation of the strategies implemented, ensuring their effectiveness and adaptability to specific needs. The proposal stands out for its practical and collaborative approach, involving the educational community in a continuous process of improvement and adaptation. It is anticipated that the results of this research will have a significant impact on educational accessibility, contributing to a more inclusive and equitable education in the IoT technology arena. This initiative not only benefits students with special needs, but also enriches the learning environment for all participants, fostering a more comprehensive and diverse approach to technology education.